Dom34 mediates targeting of exogenous RNA in the antiviral OAS/RNase L pathway. Issue 1 (5th November 2018) - Nogimori, Takuto; Nishiura, Kyutatsu; Kawashima, Sho; Nagai, Takahiro; Oishi, Yuka; Hosoda, Nao; Imataka, Hiroaki; Kitamura, Yoshiaki; Kitade, Yukio; Hoshino, Shin-ichi
Abstract: The 2′-5′-oligoadenylate synthetase (OAS)/RNase L pathway is an innate immune system that protects hosts against pathogenic viruses and bacteria through cleavage of exogenous single-stranded RNA; however, this system's selective targeting mechanism remains unclear. Here, we identified an mRNA quality control factor Dom34 as a novel restriction factor for a positive-sense single-stranded RNA virus. Downregulation of Dom34 and RNase L increases viral replication, as well as half-life of the viral RNA. Dom34 directly binds RNase L to form a surveillance complex to recognize and eliminate the exogenous RNA in a manner dependent on translation. Interestingly, the feature detected by the surveillance complex is not the specific sequence of the viral RNA but the 'exogenous nature' of the RNA. We propose the following model for the selective targeting of exogenous RNA; OAS3 activated by the exogenous RNA releases 2′-5′-oligoadenylates (2–5A), which in turn converts latent RNase L to an active dimer. This accelerates formation of the Dom34-RNase L surveillance complex, and its selective localization to the ribosome on the exogenous RNA, thereby promoting degradation of the RNA. Our findings reveal that the selective targeting of exogenous RNA in antiviral defense occurs via a mechanism similar to that in the degradation of aberrant transcripts in RNA quality control.